Paying zakat close members and giving wasiat to family members / Muthmainnah Mahassan … [et al.] - Zaihan Marican, Wan Nurul Balqis; Md Rahim, Nur Auni Huda; Zahari, Nurul Ashikin; Mahassan, Muthmainnah (2023)
Zakat worship is one of the goals of Islamic teachings in overcoming the problem of social symptoms. Zakat, one of Islam's main pillars, has become an obligation for its people to carry out the mission of improving harmonious relationships between human beings, so that, in the end, it is able to reduce the turmoil caused by life's problems. Zakat, in general, reflects a deep sense of humanity, justice, faith, and piety that the rich must exhibit. It is not good for a social being to want to live alone and ignore the difficulties and suffering of others. Despite the fact that evil frequently reigns supreme on the face of the earth, the nature and feeling of compassion and helping each other has been a culture since the existence of humans and will never disappear. As a result, zakat is an eternal obligation that was prescribed for people prior to Islam.